Isolation and identification of an alginate lyase-producing marine bacterium strain and its enzymological characteristics - TANG Haiqing; OU Changrong; ZHENG Xiaodong (浙江大学学报. 农业与生命科学版)
Alginate polysaccharide produced by marine brown algae or certain Gram-negative bacteria is a linear anionic binary copolymer of β-D-mannuronic acid (M) and α-L-guluronic acid (G) residues. Alginate lyase (EC 4.2.2.3; EC 4.2.2.11), also known as alginase or alginate depolymerase, catalyzes the degradation of alginate at the non-reducing terminus by β-elimination mechanism, forming unsaturated oligosaccharides with double bonds. Since the original description of alginate lyases about 50 years ago, more than 50 enzymes have been characterized from a variety of algae, marine invertebrates, terrestrial and marine microorganisms. As a tool enzyme to degrade alginate biologically, alginate lyase has been explored and utilized in broad fields. It has been reported that alginate lyase or its crude extract can play a pivotal role in decomposing brown seaweeds, producing alginate oligosaccharides, analyzing the fine structure of alginate, preparing protoplasts of seaweed, and reducing viscosity of alginate biofilm built up in the lungs of cystic fibrosis sufferers. To elucidate the unique properties of alginate lyase, great efforts have so far been made around enzyme production, purification, characterization, and gene recombinant and so on. In the present study, a wild marine strain capable of producing alginate lyase was screened and studied in order to develop a potential overproducing strain using a low-cost culture medium.Marine microorganisms producing alginate lyase were screened by agar plate using alginate as only carbon source. The morphological, biochemical and physiological characteristics and 16S rRNA gene were analyzed to identify the taxonomic position of strain QZ-4. The enzymological characteristics of alginate lyase from the strain QZ-4 were determined by ultraviolet (UV) method, including the optimal temperature, pH, thermal and pH stability, metal ions and ethylene diamine tetraacetic acid (EDTA) tolerance, etc.The results showed that the strain QZ-4 was a Gram-negative rod bacterium. Its suitable growth temperature ranged from 15 to 25℃ and NaCl concentration ranged from 15 to 60 g/L. Phylogenetic analysis based on 16S rRNA gene sequence comparisons indicated that the strain QZ-4 was a member of Pseudoalteromonas tetraodonis. The GenBank accession number was acquired as HM 130919. The alginate lyase was characterized as a single band by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and had the same decomposing ability on high guluronate and mannuronate polymers separately. The alginate lyase remained stable below 35℃ at the alkaline conditions. The optimal catalytic activity was showed at 40℃ and pH 7.5. The alginate lyase was activated by ions such as Mg2+, Na+, Fe3+ and Mn2+, but was inhibited by Zn2+ and EDTA. The results of kinetic studies showed that the Vmax (maximum reaction velocity) and Michaelis-Menten constant (Km) were measured individually as 0.541 U/mL and 0.051 mg/mL by Lineweaver-Burk (L-B) plot.In conclusion, the above results indicate that P. tetraodonis strain QZ-4 has a consistent alginate lyase yield and biomass at the present culture condition, compared with other alginate lyase-producing strains among the genus Pseudoalteromonas sp. The simple nutrition demand of strain QZ-4 makes a low-cost culture medium possible, and the yield of alginate lyase can reach as high as 135 U/mL in shaking flask during a short fermentation period. Therefore, the strain QZ-4 has the potential of producing alginate lyase on a large scale and further research is required to elucidate fermentation conditions and kinetics of this enzyme.